Optical coatings using filtered cathodic vacuum arc technique - Choong, Yoon Shin. (2008)
The objectives of this thesis are to stabilize the cathode source and also deposit stoichiometric aluminum oxide films. Firstly, the arc spot phenomena is study and what parameters influence the stability of the arc are conducted in experiments.